Isolation of Triterpenoid from Katemas (Euphorbia geniculata Ortega) Stem Extracted using Methanol and Its Toxicity Test - Eliza Eliza; Ricce Fatsiami; Setiawati Yusuf; Ferlinahayati Ferlinahayati (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
Katemas (Euphorbia geniculata Ortega) known as (Mexican) Fireplants, Painted Euphorbia, Japanese poinsettia is a plant belong to Euphorbiaceae or spurge family. Traditionally, this plant is used as furgative and treat dysentry. The aims of the research were to evaluate the toxicity and to isolate one of the triterpenoid extracted using methanol from the stem of this plant. The toxicity was evaluated by mortality test against armyworm larvae (Spodoptera litura). This assay was obtained by Methanol extraction at various concentrations (0, 1, 2, 3, 4 and 5%). The isolation process was conducted by series of work steps such as extraction, fractionation and purification. Structure elucidation was determined by spectroscopy techniques. Toxicity assay exhibited highest mortality at 5 % concentration with LC50 3,92%. Spectroscopy data analysis was able to identified a type of pentacyclic triterpenoid compound namely lupeol acetate.Keyword: Euphorbia geniculata Ortega, toxicity, lupeol acetate